2017
DOI: 10.3390/f8100356
|View full text |Cite
|
Sign up to set email alerts
|

Population Spatial Dynamics of Larix potaninii in Alpine Treeline Ecotone in the Eastern Margin of the Tibetan Plateau, China

Abstract: Abstract:The high-altitude treeline is known to be sensitive to climate variability, and is thus considered as a bio-monitoring indicator of climate change. However, our understanding of the population dynamics and the cumulative climate-change effects on the alpine treeline ecotone in recent decades is limited. Here, we investigated the population dynamics of Larix potainii on the southand north-facing slopes in the alpine treeline ecotone in the eastern margin of the Tibetan Plateau, China, including treelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Poor regeneration and naturally slow growing nature of Larix griffithiana are documented in subalpine forests in Sikkim Himalaya (Tambe et al 2011) and absence of seedlings and saplings of the species has been recorded in temperate forests in Lachung Range of the Sikkim Himalaya (Subba et al 2015). Similarly, fewer number (29.1%) of younger age classes individuals of Larix potaninii was reported in some studied plots in Tibet (Cui et al 2017). Previous research from MCA in Nepal documented non-uniform distribution of saplings and seedlings with absence of seedlings and saplings in 60% and 25% of the sampling plots, respectively, both being completely absent from higher elevation (3800-4000 m) (Sujakhu et al 2013).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Poor regeneration and naturally slow growing nature of Larix griffithiana are documented in subalpine forests in Sikkim Himalaya (Tambe et al 2011) and absence of seedlings and saplings of the species has been recorded in temperate forests in Lachung Range of the Sikkim Himalaya (Subba et al 2015). Similarly, fewer number (29.1%) of younger age classes individuals of Larix potaninii was reported in some studied plots in Tibet (Cui et al 2017). Previous research from MCA in Nepal documented non-uniform distribution of saplings and seedlings with absence of seedlings and saplings in 60% and 25% of the sampling plots, respectively, both being completely absent from higher elevation (3800-4000 m) (Sujakhu et al 2013).…”
Section: Discussionmentioning
confidence: 49%
“…In Nepal, trees of Larix occur in scattered stands on open soils of landslide areas (Miehe and Miehe 2000), on the depositional terraces, loose slopes, and other places prone to a higher rate of disturbance (Carpenter and Zomer 1996) including ancient moraines (Sakai and Malla 1981). The microclimate controlled by slope-climate-moisture interactions have found to cause profound impact on tree recruitment of Larix potaninii in alpine treeline ecotone in the eastern margin of the Tibetan Plateau, China (Cui et al 2017). Similarly, tree regeneration and community structure of L. potaninii was found to be influenced by the understory bamboo Fargesia denudata in the Wang Lang Natural Reserve, Sichuan, China (Taylor et al 1996).…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…smithii, Abies georgei Orr, Abies fabri and Abies faxoniana) or larch (i.e., Larix potaninii var. macrocarpa) form the primitive treelines on the sunny and shady slopes, respectively [5,19,[33][34][35][36][37]. In the northeastern TP, spruce (Picea likiangensis var.…”
Section: Tree Species and Treeline Ecotonementioning
confidence: 99%
“…The Tibetan Plateau hosts the Northern Hemisphere's highest alpine treelines [17,18], providing an ideal place to investigate relationships between alpine treelines and environmental variables from local to regional scales. Despite a similar warming trend across the plateau, local-scale and regional treeline studies have shown heterogeneous patterns of tree recruitment and treeline shift rates [5,10,[19][20][21][22][23][24]. However, spatiotemporal patterns of alpine treelines at regional scales covering diverse tree species and different climatic zones on the Tibetan Plateau have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%